(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
The preference disaggregation approach to the problem of multicriteria choice is to uncover the inherent model of choice that brings a decision unit to a conclusion in terms of an overall preference on the alternatives. In the context, the actual market shares of a class of competing products (alternatives) constitute a concise global variable originated in and reflecting the cumulative preferences of the consumer body, which affects the pattern of the market. This paper presents a systematic method to analyse the preference information cumulated in the actual market shares of competing products in terms of the criteria involved in the process of choice. The aim of this study is to present an entirely new approach to the problem of multicriteria choice and an application to analyse the market of tourist agency destination offer. In the paper outlines the market share analysis methodology for building an additive utility model in situations concerning attributes on which preferences behave monotonically. When contemporary information and communication technologies are included into the processes of choosing then electronic word-of-mouth (e-WOM) communication appears, while specific marketing messages are being created and transferred. The paper ends with some concluding remarks. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.